A forgotten philology. (June 2022) - Hunter, Thomas M.
Abstract : Richard Fox's More than words represents a sea change in the way we look at philology and textuality by decisively addressing a problem that was identified by George Lakoff and Mark Johnson in Metaphors we live by . In this work, Lakoff and Johnson developed the idea of conduit metaphors, the notion that thought is communicated by first being packaged and conveyed in script language and then unpackaged at the receiving end of communication. According to the conduit metaphor and its descendants and allies, there is an ineffable mental picture of thought, or thought as an ineffable presence in communication, that can be communicated across languages and cultural systems. While this idea has been expressed by different thinkers in different ways, in all variations of it, languages are conceived as a value-free tool for conveying a message. Some, like Walter Ong, tried to question this paradigm; but Ong's work on noetics ultimately also carried forth the old metaphor of script and language as a kind of packaging and thus did not provide us with a way to get beyond the conduit.